Interaction between B4C, 304 stainless steel, and Zircaloy-4 in H2O/H2 atmosphere at 1473 K. Issue 4 (3rd April 2018) - Gao, Xu; Sasaki, Ryosuke; Zheng, Lichun; Ueda, Shigeru; Kim, Sun-joong; Kitamura, Shin-ya; Kobayashi, Yoshinao
ABSTRACT: The control blade and the fuel rod installed in channel box melt in steam during severe accident of a boiling water reactor. In order to clarify the melting phenomena and relocation of the structural material in the core of the reactor, interaction and melting behavior among B4 C, 304 grade of stainless steel (SST), and Zircaloy-4 in atmosphere containing H2 /H2 O at 1473 K are investigated. The results showed that the reaction at the interface between B4 C and SST under H2 O atmosphere was slow and an oxidation was observed after 3600 s. Under H2 O/H2 atmosphere, the concentration of B and C in the SST increased and the SST melted. Despite the atmosphere, an oxide layer formed on the surface of Zircaloy-4, and thus the reactions proceeded slowly when the Zircaloy-4 was contacted with B4 C and SST. Under H2 O atmosphere, continuous oxidation happened to SST, and SST was partially melted. Under H2 atmosphere, the SST was also melted due to the diffusion of B and C from the B4 C. In addition, the oxidation of B4 C affected the oxidation behavior of SST and Zircaloy, and thus the oxidation and the hydroxylation of B4 C in a severe accident was discussed thermodynamically.